TEKNIK PEMBUATAN BIBLIOTHERAPY - Syamsudin, Syamsudin; Iswanti, Sri (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
The community service held the Department of Educational Psychology and Guidance, State University of Yogyakarta has two aims. First, Junior High School Teacher of Guidance have knowledge and skills about Bibliotherapy. Second, the teachers of guidance in Junior High School have high motivation to develop bibliotherapy so that they can make a bank of Bibliotherapy in MGP (Teacher of Guidance Deliberation Forum).This training has three methods. First, exchange ideas to find the problems in guidance and counseling faced by Junior High School teachers of guidance in Bantul Regency. Second, talks and discussions about bibliotherapy including their management and development. Third, discussion and training of making bibliotherapy.The success of this training was indicated by the increase ofknowledge on making the bibliotherapy and the gathering of 62 exp bibliotherapy managed by the Junior High School Teachers of Guidance Deliberation Forum in Educational Department in Bantul Regency. Key words: Training, bibliotherapy, guidance and counseling